High society secrets - Booth, Karen (Karen B.) (Booth, Karen (Karen B.). Sterling wives., 2020)
"Working at her late ex-husband's company, socialite Astrid Sterling finds new purpose. If only star architect Clay Morgan would give her a chance instead of the cold shoulder. But a truce that explodes into blinding passion leaves Astrid breathless--and torn. The single dad already has trust issues--and Astrid has a secret that could shatter everything they've built..."--Back cover.